Some estimated effects of the planned harnessing of the Ounasjoki river on reindeer husbandry - Pirkko Nieminen; Mauri Nieminen (Rangifer, 1983)
The harnessing of waterways for electrical power has caused permanent pasture losses and prevented the free movement of the reindeer herds in Finland. Many great changes occurred after construction of the two large artificial lakes of Lokka and Porttipahta (total 630 km2) in the Lappi reindeer herders association in the 1960s. The planned harnessing of the Ounasjoki river consists of 10 power plants and 2 big and 12 smaller artificial lakes (total 270 km2). The plan will have effects on the income of 1070 owners in 7 reindeer herders associations. The losses in reindeer husbandry estimated by three different methods were maximally 476, 2824 and 9900 reindeer (value of meat production 0.12 to 2.5 million FIM/year), 64 jobs and various herding buildings (value 3.9 million FIM). Two new reindeer farmes would become unusuable (0.5 million FIM) and in addition hay production from seasonally flooded fields (approx. 25 000 - 30 000 FIM/year) would be lost. The building of new forces in the reindeer herders association areas of Ounasjoki river would require 6.2 million FIM. Ounasjoen rakentamissuunnitelman mahdolliset vaikutukset porotalouteen. Abstract in Finnsish / Yhteenveto: Vesistojen valjastaminen såhkontuottoon on tuhonnut porolaitumia ja vaikcuttanut porojen vapaata liikkumista Suomessa. Tasta on hyvånå esimerkkinå Lokan ja Portipahdan tekoaltaiden (yhteenså 630 km2) rakentaminen Lapin paliskunnassa 1960-luvulta alkacn. Ounasjoen rakentamissuunnitelma kåsittåå 10 voimalaitosta ja 2 isoa ja 12 picnempåå tekoallasta (yhteenså 270 km2). Rakennussuunnitelma vaikuttaa 1070 poronomistajan talouteen 7 cri paliskunnassa. Kolmella eri mcnetelmallå laskien jouduttaisiin enimmillåån våhentåmåån 476, 2824 ja 9900 lukuporoa (lihantuotto 0,12-2,5 milj. mk/vuosi) sekå menetettåisim 64 ympårivuotista tyopaikkaa ja kocttaisiin useita eri rakennevahinkoja (arvoltaan noin 3,9 milj. mk). Kaksi uutta porotilaa jåisi kåyttokclvottomiksi (0,5 milj. mk) ja lisaksi tulvaniittyjen hcinåtuotto (noin 25 000 — 30 000 mk/vuosi) ...